Trường ứng suất Kiến tạo và các chuyển động hiện đại trong Vỏ Trái Đất trong đới hút chìm Manilan và lân cận - Dương, Nguyễn Văn; Lương, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2007)
Tectonic stress field and recent movements of the Earth’s crust in the Manila subduction zone and adjacent faults